Interannual and decadal variabilities of phytoplankton community in the Bering Sea and the Arctic Ocean: a case study of relationship with ENSO and Arctic Oscillation abnormity - Liu, Qian; Yang, Dan; Zhang, Haisheng; Lu, Bing (Frontiers in Earth Science, 2023)
We used molecular biomarkers (brassicasterol, dinosterol and C37 alkenones) measured from the surface sediments of the Bering Sea, the Chukchi Sea and the western Arctic Ocean in years of 1999 and 2010 to represent the groups of phytoplankton (diatoms, dinoflagellates and coccolithophores) and reconstruct the phytoplankton composition structure and biomass. The distribution of concentrations of three biomarkers were compatible to previous studies on measured phytoplankton, which showed that the phytoplankton biomass was most abundant in the Chukchi Sea, followed by the Bering Sea and the western Arctic Ocean, and diatoms were the dominant group. It suggests that molecular biomarkers are the suitable indicators of phytoplankton composition, structure and abundance. A record of biomarkers in a sediment core (NB01) collected at the Bering Sea in 2010 presented that the biomass of three phytoplankton groups increased in past 107 years, and their variation patterns were consistent. The synchronous increase of concentrations of phytoplankton biomarkers and cholesterol, a proxy of zooplankton biomass, implied that the primary production increased intensely in the last hundreds of years, corresponding to the trend of sea-ice melting as a result of global warming. Moreover, our results suggested that the combined effect of the anormal interannual changes of the El Niño-Southern Oscillation (ENSO) and the Arctic Oscillations (AO) played a key role in regulating the interannual and decadal variations of phytoplankton biomass and community composition, giving us an insight into the impact of atmospheric circulation on phytoplankton production and carbon flux in the Arctic seas.